2021
DOI: 10.1002/jhbp.945
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical prehabilitation: Improved liver regeneration and mitochondrial function after ALPPS operation in a rodent model

Abstract: Background To identify the role of physical prehabilitation (PP) in liver regeneration, mitochondrial function, biogenesis, and inflammatory response was investigated after associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) in a rodent model. Methods Male Wistar rats (n = 60) underwent ALPPS. Animals were divided (n = 30) to the physical prehabilitation group (PP) and sedentary group (S). The animals were exsanguinated before (0 hour) and 24, 48, 72, or 168 hours after the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…This, along with the robust energy-demanding regeneration led to an energetic imbalance [ 5 ]. Proceeding with our studies on mitochondrial function after ALPPS, we demonstrated that preoperative exercise applied as physical prehabilitation could significantly enhance mitochondrial function and biogenesis along with an even more powerful regeneration [ 6 ].…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…This, along with the robust energy-demanding regeneration led to an energetic imbalance [ 5 ]. Proceeding with our studies on mitochondrial function after ALPPS, we demonstrated that preoperative exercise applied as physical prehabilitation could significantly enhance mitochondrial function and biogenesis along with an even more powerful regeneration [ 6 ].…”
Section: Introductionmentioning
confidence: 86%
“…Mitochondrial ATP synthesis was investigated as previously described [ 6 ]. Incubation medium was supplemented with NADP+ (1.5 mM), hexokinase (2 U/ml), glucose 6-phosphate dehydrogen- ase (3.84 U/ml), 2.5 mM glucose, and 50 μM P1,P5-di(adenosine-5’) pentaphosphate (inhibitor of adenylate kinase).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations